Дендрофлора насаджень ПАТ Дніпровського агрегатного заводу м. Дніпро - Бессонова, Валентина Петрівна; Bessonova, Valentina; Джиган, Олена Петрівна; Dzhygan, Olena (Запорізький національний університет, 2018)
Вивчено видовий склад насаджень Дніпровського агрегатного заводу. Встановлено, що на промділянці зростає 174 екземпляри дерев, які відносяться до 21 виду і 13 родин. Домінуючими породами є Picea pungens і Betula pendula. Щодо діаметру штамбу та висоти найчисленнішими групами є рослини з показниками в межах від 4,1 до 8,0 см (24,2 % від загального числа дерев) та від 2,1 до 4 м (16,7 % від загальної кількості). Показано, що згідно розрахованого індексу стану деревостанів за кількістю дерев, які відносяться до різних класів життєвості, деревостан є ослабленим.The species composition and the vital state of green plantations on the territory of PJSC Dniprovsk aggregate plant in the city of Dnipro were investigated. The main emissions of this plant were sulfur dioxide and nitrogen oxides. The research was carried out in accordance with generally accepted methods on the basis of research and requirements for the registration of plantings. In total, 126 specimens of wood species grow on the industrial site of the plant. Deciduous tree were dominants and comprised 83 pcs. (65.8 % of all numbers of trees), whereas coniferous plants were 43 pcs. (34.2 %) respectively. The species composition is represented by 13 families and 21 species. The largest number of species belong to the Pinaceae family (29.4 % of the total amount of species). It was established that the largest number of specimens in the distribution of plants in height has a category 2.0–6.0 m – 32 pcs. (26.6 %), the smallest – 18.1– 22.0 m, which is 11.6 % of the total number of trees, and is represented by only three species – Picea pungens, Betula pendula and Platanus orientalis.
Dendroflora of plantations on territory of pjsc Dnipropetrovsk aggregate plant in the city of Dnipro
Keywords: ПАТ Дніпровський агрегатний завод; PAT Dniprovsky aggregate plant; зелені насадження; green plant; інвентаризація; inventory; видовий склад; species warehouse; життєвий стан; living camp